Research and development of next generation of antibody-based therapeutics - Li Jing; Zhu Zhenping (Acta Pharmacologica Sinica, 2016)
Monoclonal antibodies (mAb) are emerging as one of the major class of therapeutic agents in the treatment of many human diseases, in particular in cancer and immunological disorders. To date, 28 mAb have been approved by the United States Food and Drug Administration for clinical applications. In addition, several hundreds of mAb are being developed clinically by many biotech and pharmaceutical companies for various disease indications. Many challenges still remain, however, and the full potential of therapeutic antibodies has yet to be realized. With the advancement of antibody engineering technologies and our further understanding of disease biology as well as antibody mechanism of action, many classes of novel antibody formats or antibody derived molecules are emerging as promising new generation therapeutics. These new antibody formats or molecules are carefully designed and engineered to acquire special features, such as improved pharmacokinetics, increased selectivity, and enhanced efficacy. These new agents may have the potential to revolutionize both our thinking and practice in the efforts to research and develop next generation antibody-based therapeutics.